Studi Pertumbuhan Awal Kuya Batok (Cuoro Ambonensis) di Kolam Kehutanan UNIB serta Implementasinya sebagai Bahan Ajar Zoologi Vertebrata - Indah Maryani; Aceng Ruyani; Bhakti Karyadi; Hery Suhartoyo (University of Bengkulu, 2018)
ABSTRACT[Study of Kuya Batok (Cuoro Ambonensis) Early Growth’s in UNIB Forestry Pond and its Implementation as Teaching Materials on Vertebrate Zoology]. The goal of this study was to know the growth of C. amboinensis in the ex-situ conservation area of the University of Bengkulu Forestry Pond during the 10 weeks study and 3 weeks continuous research, to know the condition of abiotic factor C. amboinensis in ex-situ conservation area of Forest Ponds of Bengkulu University, and to know the knowledge and understanding of the students about the early growth of C. amboinensis, the conservation concept at the University of Bengkulu Forestry Pond and the change of students conservation attitude by using teaching materials. Implementation of learning adoption of existing teaching material products